2019
DOI: 10.1002/pbc.27789
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial issues for adolescent and young adult cancer patients in a global context: A forward‐looking approach

Abstract: The first decade of adolescent and young adult (AYA) oncology psychosocial care and research (2005–2015) was driven by a normative, developmental framework that assumed a generalizable life experience for AYAs that is distinct from both younger children and older adults. As we proceed through a second decade, new considerations emerge regarding diversity of life experiences as occurring within and influenced by a complex global context. The purpose of this paper is to review and provide commentary on the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 40 publications
(91 reference statements)
1
23
0
1
Order By: Relevance
“…Finally, both demographic diversity among AYA cancer survivors and technology, information, and social media use in the lives of AYAs have been flagged as key components in developing a forward-looking approach to AYA psychooncology care. 15 Therefore, the diversity among users and the plurality of contexts in which technologies are used must be critically incorporated into future studies about and implementation of technology-assisted psychosocial interventions for AYA cancer survivors. Innovative research approaches and clinical implementation strategies must account for health disparities associated with digital exclusion or ''usage access gaps'' that AYAs may face.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, both demographic diversity among AYA cancer survivors and technology, information, and social media use in the lives of AYAs have been flagged as key components in developing a forward-looking approach to AYA psychooncology care. 15 Therefore, the diversity among users and the plurality of contexts in which technologies are used must be critically incorporated into future studies about and implementation of technology-assisted psychosocial interventions for AYA cancer survivors. Innovative research approaches and clinical implementation strategies must account for health disparities associated with digital exclusion or ''usage access gaps'' that AYAs may face.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Indeed, studies have reported that over 60% of childhood and AYA cancer survivors experience adverse psychosocial, behavioral, and functional health outcomes that compromise their HRQoL for many years after completion of cancer treatment. 10 Key challenges affecting survivors' HRQoL include the following: (1) distressing experiences during active invasive cancer treatment (e.g., fear, pain, and nausea) 11,12 ; (2) psychosocial and emotional challenges both during and after treatment, including psychological distress, fear of recurrence, infertility, and reproductive/sexual health challenges [13][14][15] ; (3) limited knowledge about and engagement in survivorship care [16][17][18] ; and (4) impaired physical and functional health due to adverse and late effects of cancer treatment. [19][20][21] If left unaddressed, these challenges have been found to be associated with childhood and AYA cancer survivors' disengagement from survivorship care, reduced self-efficacy, increased risk health behaviors, including suicide, and compromised HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Generell können die sozialen Beziehungen der AYA mit Krebs durch Prioritätenverschiebung, kommunikative Barrieren und dem Wunsch, andere nicht zu belasten, bei gleichzeitigem Gefühl, nicht verstandenzuwerden,negativ beeinflusst werden [26]. [14,20,28]. Am stärksten ist der ungedeckte Bedarf an Hilfe und Beratung mit einer langfristig verminderten Lebensqualität verbunden.…”
Section: » Junge Krebspatienten Erhalten Oftmals Höhere Dosen Von Chemo-oder Strahlentherapieunclassified
“…Although this message of distinction has brought international attention and action, critics have suggested that it fails to appreciate the heterogeneity of AYAs and differences in experience depending on context [7,8]. The 15e39 year age range encompasses a spectrum of life stages, meaning the experiences of patients can vary extensively [9,10].…”
Section: Introductionmentioning
confidence: 99%